Existence of positive solutions for a third order ordinary differential system. Issue 3 (22nd January 2010) - Wang, Cai-Xun; Sun, Hong-Rui; Wang, Fang
In this paper, we consider the existence of positive solution for a class of third order ordinary differential system, where the nonlinear term is superlinear in one equation and sublinear in the other equation in some sense, by applying the fixed point index theory on the cone K1 × K2 which is the cartesian product of two cones, the existence criteria of at least one positive solutions of the system is established. An example is also given to illustrate the main result.